Aminoterminal propeptide of type I procollagen (PINP) correlates to bone loss and predicts the efficacy of antiresorptive therapy in pre- and post-menopausal non-metastatic breast cancer patients. - Saarto, T. (Nature Publishing Group|1, 1998)
The aim of this study was to determine the correlation between changes in collagen metabolites (ICTP, mature cross-linked carboxy-terminal telopeptide of type I collagen; PINP, the amino-terminal propeptide of type I procollagen) and bone mineral density (BMD) in 206 pre- and post-menopausal breast cancer patients with non-metastatic disease. All patients received adjuvant cancer treatment--premenopausal patients chemotherapy and post-menopausal patients anti-oestrogens. In addition, the patients were also randomized to receive oral clodronate 1600 mg daily for 3 years. BMD was measured at baseline and at 1 and 2 years, the collagen metabolites at baseline and at 1 year. There was a highly significant negative correlation between the changes in PINP and BMD in lumbar spine and femoral neck from baseline to 12 months in all patients (r(s) = -0.68, P < 0.0001, and -0.45, P < 0.0001, respectively), and in pre- and post-menopausal patients separately. The changes in PINP levels at 12 months predict further changes in BMD at 24 months (r = -0.70, P < 0.0001, and -0.51, P < 0.0001, respectively). ICTP and BMD changes correlated significantly only in lumbar spine of premenopausal patients who developed rapid bone loss due to chemotherapy-induced amenorrhoea (r(s) = -0.34, P = 0.0003). The PINP levels at 12 months were significantly lower in the clodronate group than in the control group (P < 0.0001). Our results indicate that PINP is a sensitive marker of bone turnover rate. Changes in PINP levels significantly predicted changes in BMD and correlated with the antiresorptive efficacy of clodronate treatment.